Complete chloroplast genome sequence of Pueraria thomsonii, an important traditional Chinese medicine plant - Xiao-Rong Miao; Jun-Qi Niu; Ai-Qin Wang; Dao-Bo Wang; Jing Fan (Mitochondrial DNA. Part B. Resources, 2019)
Pueraria thomsonii is a leguminous plant with high root yield and starch content. It is also a medicinal material in the Chinese pharmacopeia. However, the raw materials of P. thomsonii are often confused with some non-medicinal Pueraria plants. To enrich the genetic resources of P. thomsonii and guide its molecular identification, the complete chloroplast genome was sequenced and reported. The total genome of P. thomsonii is 153,434 bp in length. consisting of two inverted repeat regions (IRS, 25,640 bp each) separated by a large single-copy (LSC, 84,155 bp) and a small single-copy region (SSC, 17,999 bp). The overall GC content is 35.41%. It contains 130 genes, including 85 protein coding genes, 8 rRNA genes and 37 tRNA genes. Phylogenetic analysis showed that P. thomsonii could be distinguished from other plants and closely related to the legume Pachyrhizus erosus. This study enriches the genetic information of P. thomsonii and contributes to the screening of excellent germplasm.